Energy performance analysis of residential buildings in Bandar Anzali: Influence of orientation and aspect ratio - Peyman Naghipour; Afshin Naghipour (Next Sustainability)
This study evaluates the effects of orientation and dimensional ratio of residential buildings in Bandar Anzali City of Iran with the aim of optimizing energy consumption. Rapid urbanization and increased construction activities have led to higher greenhouse gas emissions, necessitating effective energy optimization strategies for sustainable urban development. In this research, a mixed-method approach combining quantitative and qualitative analysis was employed, utilizing advanced energy modeling and weather simulations. Design Builder and Ladybug software were used to simulate and analyze energy consumption for various dimension ratios and orientations of a four-story residential building under Anzali’s climatic conditions. The results indicate that buildings with a 1:4 aspect ratio and an east-west orientation exhibit the lowest energy consumption, reaching 166.1 kWh/m², which is 14 % lower compared to a building with a 1:1 ratio. Additionally, the north-south orientation minimizes CO₂ emissions and annual energy usage. The conclusion suggests that Proper selection of building aspect ratio and orientation significantly reduces energy consumption and enhances environmental performance, providing a pathway for sustainable building designs. This research offers practical guidelines for engineers and architects to design energy-efficient buildings, reducing costs and mitigating greenhouse gas emissions. The study introduces novel data-driven insights and practical models for designing sustainable, low-energy buildings in similar climatic regions, serving as a benchmark for future research in energy optimization.